Visible light responsive ruthenium-doped titanium dioxide for the removal of metsulfuron-methyl herbcide in aqueous phase - Senthilnanthan, M.; Ho, D.P.; Vigneswaran, S.; Ngo, H.H.; Shon, H.K. (Elsevier, 2010)
Titanium dioxide (TiO2) under UV light irradiation is one of the effective treatment methods to reduce the concentration of synthetic organic compounds in water. Nevertheless, only a small amount of UV light is absorbed in the solar light. This makes the less use of TiO2 for environmental applications. In this study, we prepared Ru-doped visible light responsive (VLR) TiO2 to improve visible light absorption and characterized it in terms of physical and chemical properties. The photocatalytic activity of VLR Ru-doped TiO2 was investigated to remove metsulfuron-methyl (MSM) in aqueous phase. The Ru-doped TiO2 at different Ru concentrations was found to have the anatase phase. The undoped and Ru-doped TiO2 consisted of regular round shape. The photocatalytic activity of VLR photocatalyst was significantly improved on the addition of Ru from 40% for undoped TiO2 to 80% for Ru-doped TiO2. The removal efficiency of MSM was proportional to the increasing Ru-doped TiO2 under visible light. As the calcined temperature increased from 300 to 900 °C, the degradation efficiencies moderately changed from 65 to 90%. However, the effect of calcination duration was marginal on the photodegradation of MSM.
Keywords: Metsulfuron-methyl; Photocatalysis; Ruthenium; Titanium dioxide; Visible light; Water purification